Target price accuracy of sell-side analysts: evidence from India - Suresh Kadam; Madhvi Sethi (Cogent Economics & Finance, 2024)
Target prices forecasted by sell-side equity research analysts play a crucial role in market participants' investment decisions. We, using a large sample for Indian markets, determine during the period and end of the period 12-month ahead target price achievements, examine the effectiveness of valuation methods for determining target prices, evaluate target price accuracy using prediction error metrics, and investigate the factors influencing target price accuracy. Our findings indicate that sell-side analysts have reasonable forecasting abilities, achieving 63% of their target prices over a 12-month forecasting horizon. The level of achievement decreased with increasing optimism in predictions. Analysts generally prefer holistic and multiple-based valuation approaches to determine the target prices. The DCF methodology was less effective than the SOTP hybrid and multiple-based approaches in predicting target prices. We find that more optimistic target prices and higher beta contribute to increased prediction errors, whereas better market returns reduce errors. Analysts struggle to predict prices for loss-making enterprises, and have difficulty forecasting target prices in capital-intensive sectors. These findings contribute to the existing body of knowledge and have significant implications for stakeholders in financial markets. The study examines the accuracy of analysts' target price forecasts and the factors influencing that accuracy. We find that analysts demonstrate reasonable forecasting abilities, with 63% of their target prices being accurate within a 12-month period. Our results suggest that analysts and brokerage firms should utilize more rigorous valuation models, such as the Sum of the Parts (SOTP) Hybrid, when setting target prices, whenever relevant. Investors should be aware of the limitations linked to analysts' stock price forecasts, particularly in capital-intensive industries, and should be cautious when considering overly optimistic target price recommendations, especially for small-cap or loss-making companies. Our insights into the impact of valuation methods and capital intensity on target price accuracy contribute new knowledge to the existing literature.
Keywords: 330; analyst recommendation; analyst reports; equity research; target price accuracy; Target prices; valuation methods